A Robust Analytical Approach for the Identification of Specific Protein Carbonylation Sites: Metal-Catalyzed Oxidations of Human Serum Albumin. (11th February 2017) - Ugur, Zafer; Gronert, Scott
ABSTRACT: The formation of protein carbonyls in the metal-catalyzed oxidation of human serum albumin (HSA) is characterized using a new analytical approach that involves tagging the modification site with multiple hydrazide reagents. Protein carbonyl formation at lysine and arginine residues was catalyzed with copper and iron ions, and the resulting oxidation patterns in HSA are contrasted. A total of 18 modification sites were identified with iron-ion catalysis and 14 with copper-ion catalysis. However, with the more stringent requirement of identification with at least two tagging reagents, the number of validated modification sites drops to 10 for iron and nine for copper. Of the 14 total validated sites, there were only five in common for the two metal ions. The results illustrate the value of using multiple tagging agents and highlight the selective and specific nature of metal-catalyzed protein oxidations.